Genetic diversity of safflower (Carthamus tinctorius L.) germplasm as revealed by SSR markers. Issue 1 (27th July 2015) - Usha Kiran, B.; Mukta, N.; Kadirvel, P.; Alivelu, K.; Senthilvel, S.; Kishore, P.; Varaprasad, K. S.
Abstract : Safflower is a multi-purpose oilseed crop, primarily known for good quality oil containing highest polyunsaturated fatty acid content (>80%) among edible oils. In this study, a core subset of 148 safflower accessions representing 15 countries, predominantly of Indian origin, was evaluated for agronomic traits and characterized for genetic diversity, population structure and linkage disequilibrium (LD) using 44 simple sequence repeat (SSR) loci across 11 linkage groups to enable its utilization in breeding and genetic mapping purposes. The collection had substantial variation for seed yield-related traits. SSR allelic variation was low as indicated by average number of alleles (3.6) per locus, gene diversity (0.314) and polymorphism information content (0.284). Cluster analysis (neighbour-joining tree) revealed five major genotypic groups with very low bootstrap support. STRUCTURE analysis showed recognizable population structure; based on membership coefficients ( ≥ 0.75), 52% accessions were classified into four populations ( K = 4) and the remaining 48% accessions into admixture group. High F st values (0.30–0.48) suggested that the populations were substantially differentiated. Analysis of molecular variance results showed that maximum of genetic variation (85%) was explained between individuals within the population suggesting that the population structure was only weak. About 1.9% of SSR locus pairs were in LD, which appeared to be low. High phenotypic variation, mild population structure and low level of LD among unlinked loci suggested that the core subset can be explored for association mapping of seed yield components in safflower.